2013
DOI: 10.1128/genomea.00671-13
|View full text |Cite|
|
Sign up to set email alerts
|

Genome Sequence of Salt-Tolerant Bacillus safensis Strain VK, Isolated from Saline Desert Area of Gujarat, India

Abstract: Bacillus safensis strain VK was isolated from the rhizosphere of a cumin plant growing in the saline desert of Radhanpar, Gujarat, India. Here, we provide the 3.68-Mb draft genome sequence of B. safensis VK, which might provide information about the salt tolerance and genes encoding enzymes for the strain’s plant growth-promoting potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…Bacillus safensis was first identified in 2006 as a contaminant from spacecraft-assembly facilities (SAF) in USA from which it derived its specific epithet safensis [25]. Bacillus safensis are salt-tolerating plant growth promoting rhizobacteria (PGPR) [26,27]. The productions of industrially important enzymes like b-galactosidase [28], endoinulinase [29], and lipases [30] by some strains of B. safensis have been reported.…”
Section: Bacterial Isolatementioning
confidence: 99%
“…Bacillus safensis was first identified in 2006 as a contaminant from spacecraft-assembly facilities (SAF) in USA from which it derived its specific epithet safensis [25]. Bacillus safensis are salt-tolerating plant growth promoting rhizobacteria (PGPR) [26,27]. The productions of industrially important enzymes like b-galactosidase [28], endoinulinase [29], and lipases [30] by some strains of B. safensis have been reported.…”
Section: Bacterial Isolatementioning
confidence: 99%
“…Bacillus safensis is a rod shaped Gram-positive, mesophilic, spore forming, aerobic and chemo-heterotrophic bacterium that has tolerance for salts, heavy metals, and ultraviolet and gamma radiations [19][20][21]. B. safensis thrives i n wide range of habitats, some of which the conditions are too unfavourable for other organisms to survive.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the species has also been reported in desert soil (2), sweet meat whey (3), root tubers (4), and rhizosphere (5). The search for potentially biodegrading microorganisms revealed that this species can also be found in petroleum samples.…”
Section: Genome Announcementmentioning
confidence: 89%